Molecular Diversity of Bacteria from Three Distinct Ecosystems within Great Smoky Mountains National Park - Collins, Melissa Brooke (2006)
The number of microbial species in nature may be in the millions, but most have never been observed or detected (Hong et al. 2006). For over 100 years, studies have focused primarily on culturing species from environmental samples in order to examine diversity of the community. With advancements in molecular techniques, a shift has occurred in both the approaches used to create community profiles and to explain what these profiles look like. This knowledge of microbial diversity is crucial for our understanding of the structure, function, and evolution of biological communities.The biodiversity of several thousand organisms has been catalogued throughout Great Smoky Mountains National Park (GSMNP) as part of a long term study call ed the All Taxa Biodiversity Inventory (ATBI). Recently, prokaryotes have become important within this study as well, and early work was focused on collecting data through culture dependent techniques.Here, I implemented a protocol, based completely on molecular techniques to create a library of species in order to describe the community of bacteria within ATBI plots. Through the use of Polymerase Chain Reaction (PCR), molecular cloning, Restriction Fragment Length Polymorphism (RFLP), and DNA sequencing I have been able to compare the diversity o f bacteria among three different ATBI plots.Identifications were made for 177 bacterial species representing eleven different phylum including Acidobocteria, Firmicutes, Actinobacteria, Bacteroidetes, Verrucomicrobia,Planctomycetes, Alphaproteobacteria, Betaproteobacteria, Deltaproteobacteria,Gammaproteobacteria, and OP1O. The community profiles detected via these methods provided a new outlook on what bacterial species were dominating these three plots compared to what the previous culture-dependent methods had suggested. Overall , the Acidobacteria and Fimricutes divisions dominated the entire community profile.Albright Grove had nine different divisions represented with the Acidobacteria dominating this site. Cataloochee and Purchase Knob both had eight different divisions represented with the Acidobacteria dominating at Cataloochee and the Proteobacteria dominating at Purchase Knob.Microorganisms are extremely important and essential for all ecosystems; yet prokaryotes are the least understood of all organisms and the least defined taxonomically.Analyzing, comparing, and identifying these different bacterial species in GSMNP provides a better understanding of microbial distribution in soil environments. This allows for a better development of bacterial taxonomy and ultimately will help in understanding bacterial niches.